AODWE-010 Severe gastrointestinal dysmotility related intestinal failure: chronic intestinal pseudo-obstruction, enteric dysmotility or a 'pragmatic' approach? experience from a national referral centre. (17th June 2017) - Vasant, DH; Kalaiselvan, R; Ablett, J; Abraham, A; Teubner, A; Paine, PA; Lal, S
Abstract : Introduction: Gastrointestinal dysmotility (GID) is a recognised cause of Type 3 Intestinal Failure (IF). Diagnosis is challenging, with uncertain merits of subclassifying into chronic intestinal pseudo-obstruction (CIPO) and Enteric Dysmotility (ED) 1 . A 'pragmatic' algorithm for GID has been proposed to address these difficulties 2 . Retrospectively, we evaluated the performance of ED/CIPO diagnostic criteria and pragmatic GID criteria in predicting outcomes of patients with 'dysmotility' requiring home parenteral nutrition (HPN). Method: Patients with primary dysmotility referred for HPN to a national IF Unit (1999–2015) were identified. 2 investigators reviewed casenotes for clinical histories, motility tests, imaging, full-thickness biopsies (FTB), breath tests, HPN and survival outcomes. Cases were excluded if they did not meet pragmatic GID criteria (morbidity + either >1 region abnormal motility test or positive FTB + small bowel (SB) involvement). Patients satisfying GID criteria were then sub-categorised into; ED (objective SB dysmotility), CIPO (ED criteria + non-mechanical SB dilatation) and 'non-CIPO/ED' if neither criteria were met. Outcomes were compared between subgroups. Results: 44 patients met GID criteria (median age 40, 30 females, 18/44 with abnormal FTBs (myopathy n=12, neuropathy n=6) and median follow-up 5 years)), whereas 7 patients not meeting pragmatic criteria were excluded. HPN improved BMI (median pre 18.3 vs. post 21.2 kg/m 2, p=0.01). HPN outcomes: survival at 1, 5 and 10 years was 95%, 77% and 47%, median catheter-related blood stream infection rate (CRBSI) 0.5/1000 days, and 18% achieved HPN independence. 25/44 (57%) met criteria for CIPO, 12/44 (27%) ED and 7/44 (16%) were 'non-CIPO/ED' patients that met GID criteria. CIPO was associated with bacterial overgrowth (13/25 vs. 3/19, p=0.03), and HPN dependency (1/25 weaned off HPN vs. 7/19, p=0.01) when compared to the ED and 'non-CIPO/ED' groups. Other factors including the yield of FTBs, opiate-dependence and HPN complications (CRBSI, IF associated liver disease and catheter related venous thromboses) did not significantly differ between the three groups. Conclusion: Our data emphasise important prognostic implications of CIPO diagnosis in the IF/GID population as a predictor of HPN dependency. Combining pragmatic evidence-based criteria with imaging to exclude CIPO is likely to give the maximum diagnostic and prognostic yield across the spectrum of GID. References: . Wingate, et al. Journal of Gastroenterology and Hepatology200217:S1–S14 . Paine, et al. Alimentary pharmacology & therapeutics201338(10):1209–1229. Disclosure of Interest: None Declared